1998
DOI: 10.1046/j.1423-0410.1998.7530230.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Examples of an Inseparable Antibody That Reacts Equally Well with DW+ and Rh32+ Red Blood Cells

Abstract: We suggest that amino acids encoded by nucleotides at the junction of exon 4 of RHD to exon 5 of RHCE may induce a conformation that is recognized by these equally reactive inseparable antibodies. Until such time that the epitope recognized by these antibodies is defined, we recommend use of the descriptive name anti-DW/Rh32.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…More recently, her RBCs were agglutinated by a serum containing an inseparable anti-D W /Rh32. 8 This suggested that her RBCs carry a novel low-prevalence antigen and that the molecular background for the D(C)C W (e)/D--phenotype in this family was different from those previously reported. The purpose of this study was to determine the molecular basis of the Rh phenotype in this well-studied serologic case.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…More recently, her RBCs were agglutinated by a serum containing an inseparable anti-D W /Rh32. 8 This suggested that her RBCs carry a novel low-prevalence antigen and that the molecular background for the D(C)C W (e)/D--phenotype in this family was different from those previously reported. The purpose of this study was to determine the molecular basis of the Rh phenotype in this well-studied serologic case.…”
contrasting
confidence: 66%
“…NR has been studied several times over the years, deposits autologous units for transfusion, and, as a nurse, has remained interested in her unusual phenotype. More recently, her RBCs were agglutinated by a serum containing an inseparable anti‐D W /Rh32 8 . This suggested that her RBCs carry a novel low‐prevalence antigen and that the molecular background for the D(C)C W (e)/D‐‐ phenotype in this family was different from those previously reported.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Most anti -D w , however, also react with Rh:32 cells, some reacting only weakly with the Rh:32 cells and some reacting as strongly with Rh:32 cells as with D w + cells [552] . Most anti -D w , however, also react with Rh:32 cells, some reacting only weakly with the Rh:32 cells and some reacting as strongly with Rh:32 cells as with D w + cells [552] .…”
Section: Alloanti-dmentioning
confidence: 94%
“…LFAs are immunogenic and antibodies to RH23 (D W ) and Rh32 can cause hemolytic disease of the fetus and newborn . Formation of these LFAs is thought to be due to the interaction of amino acids encoded by RHD Exon 4 and RHCE Exon 5 . DV and DBT cells are defined by two distinct characteristic patterns of reaction against a panel of anti‐D MoAbs …”
mentioning
confidence: 99%